2015
DOI: 10.1180/minmag.2015.079.4.01
|View full text |Cite
|
Sign up to set email alerts
|

Metallogeny of the North Atlantic Craton in Greenland

Abstract: The North Atlantic Craton (NAC) extends along the coasts of southern Greenland. At its northern and southern margins, Archaean rocks are overprinted by Palaeoproterozoic orogeny or overlain by younger rocks. Typical granite-greenstone and granite-gneiss complexes represent the entire Archaean, with a hiatus from ∼3.55–3.20 Ga. In the granulite- and amphibolite-facies terranes, the metallogeny comprises hypozonal orogenic gold and Ni-PGE-Cr-Ti-V in mafic-ultramafic magmatic systems. Gold occurrences are widesp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 114 publications
1
3
0
Order By: Relevance
“…This underlines the possibility that high-grade metamorphic events, such as the Badcallian in the LGC, may obscure temporally and/or petrogenetically distinct magmatic events, as may be typical in marginal cratonic regions (such as the LGC, within the wider NAC). This supports the study of Kolb et al (2015), who identified multiple episodes of Archean ultramafic-mafic magmatism in the Greenlandic portion of the NAC.…”
Section: Ben Strome and Geodh' Nan Sgadan: Evidence For Multiple Ultrsupporting
confidence: 90%
“…This underlines the possibility that high-grade metamorphic events, such as the Badcallian in the LGC, may obscure temporally and/or petrogenetically distinct magmatic events, as may be typical in marginal cratonic regions (such as the LGC, within the wider NAC). This supports the study of Kolb et al (2015), who identified multiple episodes of Archean ultramafic-mafic magmatism in the Greenlandic portion of the NAC.…”
Section: Ben Strome and Geodh' Nan Sgadan: Evidence For Multiple Ultrsupporting
confidence: 90%
“…The main orthomagmatic mineral systems formed at ca. 2970-2950 Ma and are relatively old compared to their counterparts in Australia and Canada (Cawood and Hawkesworth, 2015;Kolb et al, 2015). Only small VHMS occurrences are known, probably because of the weak preservation potential in the deeper crust (Fig.…”
Section: Summary Of the Metallogenic Evolution Of Greenlandmentioning
confidence: 97%
“…Most of the Archean rocks are at amphibolite facies or granulite facies metamorphic grade. Middle to deep crustal processes define the preservation potential and the mineral systems for possible ore deposits and mainly three types are known (Kolb et al, 2015): (1) orthomagmatic deposits with mineralization of Cr-Ti-V-Ni-PGE-Au;…”
Section: Summary Of the Metallogenic Evolution Of Greenlandmentioning
confidence: 99%
“…More recent reviews focus on specific metallogenic provinces in Greenland that are systematically related to a variety of geological terrains: Steenfeldt et al (1997) on South Greenland and more recently by Stendal et al (2005), and Kolb et al (2015Kolb et al ( , 2016Kolb et al ( , 2017 covering most of the geological terrains in Greenland.…”
Section: Key Reviews Of Mineral Occurrences and Deposits In Greenlandmentioning
confidence: 99%